CONTINUOUSLY CYCLIC CASTING BY FROSTING IS AN EFFECTIVE TECHNOLOGY OF THE HIGH-QUALITY SLUGS PRODUCTION - A. M. Bodjako; V. F. Bevza; S. V. Galagaev (Литьë и металлургия)
The results of investigations in the field, of structure formation and characteristics of castings, produced by means of continuously-cyclic casting by directional hardening of white high-chromium, grey, high-test cast irons and examples of their practical application are given.